Ecological problems and nitrogen balance in vegetable crops growing - Tsetska Simeonova; Dimitranka Stoicheva; Petra Alexandrova (Eurasian Journal of Soil Science, 2015)
The purpose of this study is to focus on the nitrogen balance and losses in agricultural system. The influence of precipitation, irrigation and fertilizer application on some soil parameters, N-uptake by plant production and N-output by lysimetric water are evaluated in this paper.The study is carried out on Fluvisol, near Plovdiv in Southern Bulgaria under the conditions of field experiments with different vegetable crops (eggplant, green beans and carrots) over the period 2009-2011. The experimental design includes 3 treatments with nitrogen application –N0, N80 and N160 on the background of P80K80 kg.ha-1. The field plots are equipped with modification of Ebermayer type of lysimeters, which collect water from 100 cm depth of soil profile.According the received data it was observed that compensation between the amounts of N input and output was achieved in two variants (N80, N160) for all crops growing. Reducing the nitrogen input to the amount applied by precipitation and irrigation waters is the most ecological-friendly technological decision and very important factor for environment protection.